Reviewing the intervention of landscape in vertical greenery systems (VGSS) - Othman, Jamilah; Othman, Rashidi; Mohd Hatta, Farah Ayuni (AESS Publications, 2020)
Concern for green technologies with efforts to strive for the quality environment can be achieved via VGSs. The systems provide multiple benefits by restoring greenery in urban landscapes. In general, they help improving environmental, social, economic, and ecological values. Green technologies have been in the industry for more than a decade. However, the contribution from the landscape architecture circles is found insufficient. Hence, for a start, this paper reviews the intervention of landscape in VGSs from the aspects of system operation, plant component, and landscape maintenance. The aim is to create an eye-opener amongst the experts, whose expertise in similar studies can assist in sustaining the usage and lifecycle of the systems. Both reviews of literature and personal observations traced the necessary data having concentrated on green wall and living wall. Information on the operational nomenclatures of VGSs is useful to reduce confusion amongst researchers and academics. Simple insights of this study would encourage in-depth explorations in the areas of the landscape. Consideration to opt for local plant species of the tropical climate is a convincing topical topic suggested for future research.